The Boy Fortune Hunters in Yucatan - Baum, L. Frank (Saga Egmont, 2021)
Originally published under the pseudonym Floyd Akers, ‘The Boy Fortune Hunters in Yucatan’ is the fifth in the children’s adventure series by prolific author L. Frank Baum. We pick up with our three heroes Sam, Archie, and Joe as they search for the lost city of Tcha deep in the Yucatan jungle, where rumour has it there is treasure hidden beyond anyone’s wildest imagination. With the help of their guide Chaka, the group must evade bandits, natural disasters, and even human sacrifice as they seek out the legendary city and its’ hidden treasure.